The impact of group music therapy on anxiety, stress, and wellbeing levels, and chemotherapy-induced side effects for oncology patients and their caregivers during chemotherapy: a retrospective cohort study - Andrés Salgado-Vasco; Juliana Torres-Morales; Clara Inés Durán-Rojas; Lucy Yolima Beltrán-Sánchez; Moshé Amarillo; Mark Ettenberger (BMC Complementary Medicine and Therapies)
Abstract Introduction Cancer is currently the second most common cause of death worldwide and is often treated with chemotherapy. Music therapy is a widely used adjunct therapy offered in oncology settings to attenuate negative impacts of treatment on patient’s physical and mental health; however, music therapy research during chemotherapy is relatively scarce. The aim of this study is to evaluate the impact of group music therapy sessions with patients and caregivers on their perceived anxiety, stress, and wellbeing levels and the perception of chemotherapy-induced side effects for patients. Materials and methods This is a retrospective cohort study following the STROBE guidelines. From April to October 2022, 41 group music therapy sessions including 141 patients and 51 caregivers were conducted. Participants filled out pre- and post-intervention Visual Analogue Scales (VAS) assessing their anxiety, stress, and wellbeing levels, and for patients the intensity of chemotherapy-induced side effects. Results The results show a statistically significant decrease of anxiety and stress levels (p < .001), an increase in well-being of patients and caregivers (p < .001, p = .009), and a decrease in patients’ perceived intensity of chemotherapy-induced side effects (p = .003). Calculated effect sizes were moderate for anxiety, stress, and well-being levels, and small for chemotherapy-induced side effects. Discussion This is the first study regarding group music therapy sessions for cancer patients and their caregivers during chemotherapy in Colombia. Music therapy has been found to be a valuable strategy to reduce psychological distress in this population and to provide opportunities for fostering self-care and social interaction. Conclusions Music therapy should be considered as a valuable complementary therapy during chemotherapy. However, it is crucial to conduct prospective studies with parallel group designs to confirm these preliminary findings.